2010
DOI: 10.4103/0972-124x.65439
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of micronutrient status in the serum of diabetes mellitus patients and healthy individuals with periodontitis

Abstract: Background:Periodontal diseases are microbial induced chronic inflammatory conditions characterized by infiltration of leukocytes, loss of connective tissue, alveolar bone resorption, and formation of periodontal pockets. In response to periodontal pathogens, the leukocytes (PMN) elaborate destructive oxidants, proteinases and other factors. The balance between these factors, the antioxidants and endogenously synthesized antiproteinases determine the extent of periodontal damage. Diabetes mellitus is a metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 6 publications
(5 reference statements)
1
38
0
Order By: Relevance
“…It is therefore quite possible that periodontitis causes lower plasma vitamin C through this mechanism [39]. In this study serum vitamin C level was lower in chronic periodontitis as compared to healthy controls, which was also documented by [40,41].Smokers are constantly over exposed to free radicals through inhalation of long lived carbon and oxygen centered radicals that subsequently deplete the plasma antioxidant vitamin C. Similar to our study, studies [42,43] have reported lower vitamin C levels in smokers than in non-smokers.…”
Section: Discussionsupporting
confidence: 73%
“…It is therefore quite possible that periodontitis causes lower plasma vitamin C through this mechanism [39]. In this study serum vitamin C level was lower in chronic periodontitis as compared to healthy controls, which was also documented by [40,41].Smokers are constantly over exposed to free radicals through inhalation of long lived carbon and oxygen centered radicals that subsequently deplete the plasma antioxidant vitamin C. Similar to our study, studies [42,43] have reported lower vitamin C levels in smokers than in non-smokers.…”
Section: Discussionsupporting
confidence: 73%
“…The results of the levels of glutathione and catalase were found to be significant, which are consistent with the outcomes of other studies. [12347]…”
Section: Discussionmentioning
confidence: 99%
“…[2] There is also a clearly defined and substantial role for ROS in periodontitis. [4] Antioxidants are substances that delay or prevent the oxidation of cellular oxidizable substrates.…”
Section: Introductionmentioning
confidence: 99%
“…[456] Sprren Kiilerich et al . [7] observed that Zn absorption decreases in diabetes, thereby leading to its intracellular depletion.…”
Section: Introductionmentioning
confidence: 99%